Pentingnya Peran Pendidikan terhadap Kinerja Pelaut Ditinjau dari Tingkat Pendidikan dan Status Pernikahan - Utami, Dessy Nur; Nurahaju, Rini (Universitas Hang Tuah, 2019)
The purpose of this study is to find out how seafarers think about how important the role of education is to seafarers' performance when viewed from the education level and marital status of the seafarers themselves. A s the subjects of the study were 69 active seamen who were studying in a polytechnic. The results of the study processed with the chi-square test showed that when viewed from the level of education of seafarers, they stated that education did not play a significant role in its performance. Conversely, if viewed from the status of marriage, married seafarers consider that education plays an important role while marriages who are not married consider that education does not play a significant role in seafarers' performance.